2021
DOI: 10.1177/2333794x21999152
|View full text |Cite
|
Sign up to set email alerts
|

Predicting Candida Infection in Pediatric Intensive Care Unit using Candida Score in a Low-Resource Setting

Abstract: Candida infection was previously thought to be rare in intensive care. With the increased use of broad-spectrum antibiotics, the incidence of candida infection increased significantly. Case-control study was done in patients ≤18 years of age treated for 3 days or more in Pediatric Intensive Care Unit (PICU) Dr. Sardjito General Hospital, Yogyakarta from January 2014 to December 2016. Overall, 43 children were included in this study as a case group with positive candida culture and 43 children as a control grou… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 18 publications
1
1
0
Order By: Relevance
“…Due to the common use of fluconazole in empiric antifungal prophylaxis in high-risk premature infants, an increased colonization of the gastrointestinal tract with Candida non-albicans was observed. The main pathogens were Candida parapsilosis (increase in all the studied years except 2017) and Candida glabrata in 2019 and 2020, which is in accordance with data published in the literature [8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…Due to the common use of fluconazole in empiric antifungal prophylaxis in high-risk premature infants, an increased colonization of the gastrointestinal tract with Candida non-albicans was observed. The main pathogens were Candida parapsilosis (increase in all the studied years except 2017) and Candida glabrata in 2019 and 2020, which is in accordance with data published in the literature [8][9][10][11][12][13].…”
Section: Discussionsupporting
confidence: 89%
“…A male predominance in pediatric candidemia cases has been noted in previous studies but was not considered and calculated as a separate independent predictive risk factor. 19,44,45 This variable was significant in our study where 77% of infected children were males. It should be noted, however, that another study reported a female predominance.…”
Section: Risk Factors For Candidemiamentioning
confidence: 61%